SOLID MATRIX PRIMING IN COFFEE SEEDS STORED WITH HIGH MOISTURE - Machado Carvalho, Carlos Alberto; Mendes Guimarães, Renato; de Almeida Silva, Tanismare Tatiana (Coffee Science - ISSN 1984-3909, 2012)
The water content of seeds and temperature affect the biological processes, determining different results when seeds areexposed to different levels of these factors. When seeds are subjected to priming, we expect improvement in the physiological qualityof seeds, but while promising, this procedure is still in the experimental phase in coffee seeds. In order to evaluate the effects of solidmatrix priming at three different temperatures to evaluate the performance of coffee seeds (Coffea arabica L.) stored for up to twelvemonths, we carried out this research at the Central Laboratory of Seed Analysis in the Agriculture Department, Universidade Federalde Lavras, Lavras - MG. Seeds with 36.0% moisture content were sorted, processed, packed in polyethylene bags and kept in coldstorage for up to 12 months. At quarterly intervals, the seed samples were subjected to solid matrix priming, at temperatures of 20 °C,30 °C and 40 °C for 6 days. One control, without priming, was also evaluated. The physiological conditioning of solid matrix primingof C. Arabica seeds, held for 6 days at 20 °C and 30 °C favors the emergence of seedlings in seeds stored for 9 months and under 40°C, is harmful to the C. arabica seeds.